Intranasal Delivery of a Silymarin Loaded Microemulsion for the Effective Treatment of Parkinson’s Disease in Rats: Formulation, Optimization, Characterization, and In Vivo Evaluation - Mohd Imran; Mazen Almehmadi; Ahad Amer Alsaiari; Mehnaz Kamal; Mohammed Kanan Alshammari; Mohammed Omar Alzahrani; Faisal Khaled Almaysari; Abdulrahman Omar Alzahrani; Ahmed Faraj Elkerdasy; Sachin Kumar Singh (Pharmaceutics, 2023)
A mucoadhesive microemulsion of lipophilic silymarin (SLMMME) was developed to treat Parkinson’s disease (PD). Optimization of the SLM microemulsion (ME) was performed using Central Composite Design (CCD). The composition of oil, surfactant, co-surfactant, and water was varied, as per the design, to optimize their ratio and achieve desirable droplet size, zeta potential, and drug loading. The droplet size, zeta potential, and drug loading of optimized SLMME were 61.26 ± 3.65 nm, −24.26 ± 0.2 mV, and 97.28 ± 4.87%, respectively. With the addition of chitosan, the droplet size and zeta potential of the developed ME were both improved considerably. In vitro cell toxicity investigations on a neuroblastoma cell line confirmed that SLMMME was non-toxic and harmless. In comparison to ME and drug solution, mucoadhesive ME had the most flow through sheep nasal mucosa. Further, the in vitro release showed significantly higher drug release, and diffusion of the SLM loaded in MEs than that of the silymarin solution (SLMS). The assessment of behavioral and biochemical parameters, as well as inflammatory markers, showed significant (p < 0.05) amelioration in their level, confirming the significant improvement in neuroprotection in rats treated with SLMMME compared to rats treated with naïve SLM.